Phenological growth and development stages of asparagus pea (Tetragonolobus purpureus Moench.) under different sowing patterns in the conditions of the Right-Bank Forest-Steppe of Ukraine - I. Bobos; O. Komar; I. Fedosiy; A. Matvienko (Рослинництво та ґрунтознавство)
The study synthesised data on the application of phenological models to develop adaptive production technologies for asparagus pea, enabling the regulation of phenological phase progression while considering the unique characteristics of the cultivar and regional conditions. This approach is crucial for improving both yield and quality across various ecological conditions. The study aimed to determine the rate of key growth and development phases of asparagus pea and to establish the dependence of these processes on specific cultivation technology elements, particularly sowing patterns, in the Right-Bank Forest-Steppe of Ukraine. A comprehensive approach was employed, integrating field research on cultivation practices, visual observations of plant development dynamics, and statistical analysis to quantify the impact of various factors. The findings revealed a correlation between sowing patterns and the duration of phenological phases. In the 45 × 10 cm and 45 × 15 cm (control) variants, emergence occurred on 11 May, 11 days after sowing, under a cumulative temperature above 10°C of 59.4°C and 45 mm of precipitation. In the 45 × 20 cm and 45 × 25 cm variants, emergence was recorded on 17 May, 13 days after sowing, with a cumulative temperature of 71.2°C and 45.7 mm of precipitation. The onset of flowering was recorded between 16 and 23 June, depending on plant density. The shortest “emergence-flowering” period was observed in the 45 × 10 cm variant (32 days), with a cumulative temperature of 252.9°C and 84.5 mm of precipitation, while the longest was in the 45 × 25 cm variant (37 days), with a cumulative temperature of 328.5°C and 92.7 mm of precipitation. The onset of the technical maturity stage was noted between 24 June and 5 July, with the “flowering-technical maturity” period ranging from 8 to 12 days, depending on plant density. Biological maturity occurred between 10 and 18 July, with the “technical-biological maturity” phase lasting 12-16 days. The growing season lasted 56-62 days, with a cumulative temperature of 534-619.9°C and precipitation levels of 156-169.7 mm. A strong inverse correlation was established between plant density and the duration of the interphase periods from sowing to technical maturity (r = -0.84 to -0.98), while a strong direct correlation was observed between density and the “technical-biological maturity” period (r = 0.92). Increasing plant density by 5,000 plants per hectare shortened phenological periods by 0.8-2 days. A direct correlation was also identified between precipitation (r = 0.86 to 1.0), temperature (r = 0.97 to 1.0), and phase duration. A temperature increase of 10°C extended the phases by 0.6-1.7 days. The findings provide a basis for optimising sowing patterns to enhance plant growth and development, thereby improving asparagus pea productivity